2014
DOI: 10.1371/journal.pone.0092014
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Task Shifting for Antiretroviral Treatment Services in Namibia: Implementation Research to Move Evidence into Action

Abstract: BackgroundEvidence from several sub-Saharan countries support nurse-initiated antiretroviral treatment as a feasible alternative to doctor-led models characteristic of early responses to the HIV epidemic. However, service delivery models shown to be effective in one country may not be readily adopted in another. This study used an implementation research approach to assist policy makers and other stakeholders to assess the acceptability and feasibility of task shifting in the Namibian context.MethodsThe Namibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
3
13
0
1
Order By: Relevance
“…The study found a 15% lower cost of visit and 16% lower length of visit for ART patients treated by nurses and health officers, as compared with the physicians. The findings from the econometric model support the recent debate on task shifting (Zachariah et al 2009, O'Malley et al 2014, Edge 2008 health care delivery to the least costly health worker and who is capable of reliably performing this task. This micro-economic analysis strengthens recent findings on antiretroviral task-shifting in Namibia and Botswana which highlighted the relevance of task shifting in improving access, service quality and skills enhancement (O'Malley et al 2014, Monyatsi et al 2013.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The study found a 15% lower cost of visit and 16% lower length of visit for ART patients treated by nurses and health officers, as compared with the physicians. The findings from the econometric model support the recent debate on task shifting (Zachariah et al 2009, O'Malley et al 2014, Edge 2008 health care delivery to the least costly health worker and who is capable of reliably performing this task. This micro-economic analysis strengthens recent findings on antiretroviral task-shifting in Namibia and Botswana which highlighted the relevance of task shifting in improving access, service quality and skills enhancement (O'Malley et al 2014, Monyatsi et al 2013.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies in Sub-Saharan Africa countries, including Ethiopia, have reviewed the relationship between task performance, access and task shifting (Gessessew et al 2011, O'Malley et al 2014, however, there is limited knowledge on the economic significance associated with ART task shifting for policy makers. More importantly, there is a paucity of evidence on the application of micro-econometric modeling to ART task-shifting.…”
Section: Objectivementioning
confidence: 99%
“…Task shifting has been shown to be effective in improving maternal health care provision for patients in LMICs, most notably in the administration of ARV therapy [ 113 , 114 ], non-communicable disease management [ 115 117 ], and mental health care [ 118 ]. Task shifting interventions involve equipping a cadre of staff in the health care system with the appropriate skills to provide services that would otherwise be provided by higher cadre providers, who are often scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Strengthening the capacity of rural healthcare agents and medical personnel was essential: the former undertook monitoring of medication adherence and ADRs, whereas the in situ participation of physicians was restricted to treatment indication, clinical exams and improved ADR management. In remote areas of Africa, transference of treatment initiation and monitoring of HIV patients to local nurses improved the access to and quality of health care and cost-effectiveness of integrated interventions [ 51 , 52 ]. Benznidazole was available at the time of our program and timely provision was carefully planned, but these usually are major issues elsewhere.…”
Section: Discussionmentioning
confidence: 99%